Algumas relações entre a psicanálise freudiana e os preceitos do “cuidado de si”e do “conhecimento de si” - Naldinho, Thiago Canonenco (Universidade Federal de São Carlos, 2018)
Our thesis is a response/comment to the question raised by Michel Foucault about what the link of psychoanalysis with the theme of spirituality would be. To that end, we begin our discussion with an analysis of a description made by the aforementioned French philosopher. He portrays the differences between two sorts of relationships between subject and truth – regarding two regimes of subjectivation: one previous and other posterior to what Foucault calls the Cartesian moment, which marks the entrance of the history of truth into the Modern Age. Later, we focus on the thought of Sigmund Freud, in order to find evidence concerning the supposed presence (stated by Foucault), at the core of psychoanalytic knowledge, of the same points that guided the millennial tradition of spirituality – the work upon the self (performed by the subject with the aim of achieving the change of his being) as a condition to accessing the truth; and the consequent transfiguration and salvation of the subject, due to its contact with the truth. Finally, we evaluate whether the presumed existence of these spiritual contents sanctions the consideration of psychoanalysis as a type of spirituality in the present time, through its relations with the old principles of self-knowledge and care of the self.
Some relations between freudian psychoanalysis and the precepts of "care of the self" and of "self- knowledge"
Keywords: Psicanálise; Cuidado de si; Conhecimento de si; Psychoanalysis; Care of the self; Self-knowledge; Freud, Sigmund, 1856-1939; Foucault, Michel, 1926-1984; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA